Socio-economic status and husbandry practices of indigenous goat rearing community in Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The research was conducted of a indigenous goat rearing community named “Deshi Chaagol Palon Mohila Somoby Somity Ltd” at three villages namely Pachpai, Borochala and Gangatia under Bhaluka Upazilla, Mymensingh district. Fifty (50) farmers were selected randomly in the study area to conduct baseline survey with help of well organized questionnaire which developed through Participatory Rural Appraisal (PRA). Data were analyzed using Statistical Package for the Social Sciences (SPSS) version 17.0. Among livestock, 31 % goat, 29% chicken and 28% cattle were reared in the project areas. 49% goats were solid Black and 36% were Black Boiragi. The profession of the farmer was agriculture (80%). The education level of the farmers was 32% illiterate and 36% were also completed primary education (1-5 class). The average family size, annual income and land size were 4.28±0.15, 83910.00±4330.61 Tk. and 45.78±6.12 decimal, respectively. Farmer’s goat rearing experience was 11.70±1.05 years. Maximum farmers (76%) were reared their goats by semi-intensive systems. Development of data based on socio-economic status of farmers during this study might help in decision making on evaluation of performance of goat at farmer’s community.Asian Australas. J. Biosci. Biotechnol. 2018, 3 (1), 11-16